Numerical Study on the performance of a heat pump-driven-DCMD for sustainable desalination - Oh, Seung Jin; Kim, Yeongmin; Hong, Youngsun; Kim, Jong Woo; Kang, Byungchan (Frontiers in Energy Research, 2022)
The study presents an energy-efficient desalination system that combines direct contact membrane distillation (DCMD) and a heat pump to improve thermal efficiency and integrate with photovoltaics. DCMD is a sort of thermal desalination process, and it requires a lot of thermal energy. A heat pump is a device that produces both hot and cold energy simultaneously with less electrical energy input compared to other heating devices, such as a boiler and an electrical heater. A hollow-fiber DCMD and a 10-kW water-to-water heat pump were considered for a numerical simulation in this study. Numerical models were established for each device and validated against the results obtained from the literature. The simulation was first carried out to identify the performance of the system based on the baseline. After that, a series of simulations were carried out in order to investigate the performance of the proposed system in terms of specific energy consumption (SEC), gained output ratio (GOR), and the coefficient of performance (COP) under various operating conditions. Results showed that the minimum SEC and the maximum GOR were achieved at the inlet feed water temperature of 66.5°C with a mass flow rate of 20 kg/min and the inlet permeate temperature of 19.8°C with a mass flow rate of 10 lpm. On the other hand, it was found that the maximum COP can be observed at the inlet feed water temperature of 23.6°C with a mass flow rate of 10 lpm and at the inlet permeate temperature of 8.9°C with a mass flow rate of 20 lpm.